Confronting budget deficits - Coleman, Rozlyn (IMF WashingtonUS, 1996)
Focuses on why deficits persist and describes major policy options available to industrial countries to reduce deficits. Looks at the budgetary issues in developing countries which differ from those in industrial countries.